STRATEGI SEKOLAH DIBAWAH NAUNGAN MA’ARIF DALAM MENCARI SISWA BARU - Arifah, Zaidatul (Jurnal Ilmiah Citra Ilmu, 2022)
The aim of this research is to find out what strategies the teacher does in finding new students at MI Qomarul Huda Banaran. This research is a qualitative research. This qualitative research is more specifically directed at the use of the case study method. Case study data can be obtained from all parties concerned, in other words, this study is collected from various sources. Data collection techniques using interview and observation techniques. The data analysis technique used in this study is an interactive model which classifies data analysis through data reduction and data display. The results showed that in increasing the number of students the form of public relations strategy carried out by MI was by kinship, the meaning was that the school with siblings could be included in the school, or the closeness that existed between the teacher and the community which ultimately made the community choose to send their children there.